Harnessing synergy: a holistic review of hybrid renewable energy systems and unified power quality conditioner integration - Nagaraju Samala; Chandramouli Bethi (Journal of Electrical Systems and Information Technology)
Abstract This comprehensive review explores the growing importance of sustainable energy solutions, with a particular focus on the integration of solar and wind technologies within hybrid renewable energy systems. As the demand for clean energy increases, hybrid systems offer a promising solution to address energy security and environmental concerns. However, these systems face significant challenges, including intermittency issues and the complexity of integration into existing power grids. This paper examines the role of hybrid systems in mitigating these challenges and improving grid stability. Additionally, it highlights the role of the unified power quality conditioner in managing power quality and facilitating the integration of renewable sources into distribution networks. Drawing from over 395 research papers, the review offers valuable insights into the current state of the field and presents key directions for future research and practical applications.